2008
DOI: 10.1007/s10508-007-9304-y
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal (Coitus Interruptus) as a Sexual Risk Reduction Strategy: Perspectives from African-American Adolescents

Abstract: This study examined adolescents' beliefs about the benefits and risks of withdrawal (coitus interruptus) with respect to both pregnancy and sexually transmitted infections (STIs). In the course of qualitative interviews with African-American youth aged 14-19 (n = 124) about sexuality and risk, 24 adolescents spontaneously introduced the subject of withdrawal as a sexual risk reduction strategy. Eighteen percent of the sexually experienced adolescents mentioned their own use of withdrawal as a contraceptive met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 31 publications
5
30
0
Order By: Relevance
“…Akin to non-homeless adolescents, this study found that homeless youth with anti-pregnancy attitudes were more likely to use effective contraception 23,32 and withdrawal, 45 implying that youth who do not want to become pregnant are utilizing contraception with a range of effectiveness to minimize the likelihood of conception. However, homeless youth in this sample report a much lower rate of using highly effective contraceptive methods, and a greater rate of using condoms, withdrawal, or no method, in comparison to previous research with non-homeless adolescents.…”
Section: Discussionmentioning
confidence: 81%
“…Akin to non-homeless adolescents, this study found that homeless youth with anti-pregnancy attitudes were more likely to use effective contraception 23,32 and withdrawal, 45 implying that youth who do not want to become pregnant are utilizing contraception with a range of effectiveness to minimize the likelihood of conception. However, homeless youth in this sample report a much lower rate of using highly effective contraceptive methods, and a greater rate of using condoms, withdrawal, or no method, in comparison to previous research with non-homeless adolescents.…”
Section: Discussionmentioning
confidence: 81%
“…Most women who were using highly effective methods reported that withdrawal was used at the same time, suggesting that many were “doubly protected” from the risk of pregnancy. It may also be possible that male partners were unaware of women’s use of hormonal contraception or were using withdrawal out of personal preference for their own reassurance [13;18]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the withdrawal method is a long-term correct adjective method which is used regardless of the opportunity to access modern contraceptive methods. 18,19 It was indicated in many studies that the withdrawal method is still regarded as an effective family planning method and, even if it leads to unwanted pregnancies there is no change in the attitudes and behaviors of families towards the method. 20,21 While the withdrawal method is an ineffective method, it is frequently used due to several cultural and personal reasons while more effective methods have a low usage rate.…”
Section: 14mentioning
confidence: 99%